Evaluación de la cinética y movilidad espermática de verracos en condiciones tropicales - Valverde-Abarca, Anthony; Zambrana-Jiménez, A.; Madrigal-Valverde, M. (Actas Iberoamericanas de Conservación Animal (AICA), 2018)
Sperm motility is linked to the energy level of the reproductive cell. The aim was to determine the influence of breed on reproductive variables of semen quality, kinetics and motility. Data were collected from 524 ejaculates of from 72 boars with mean age of 26.8±14.4 months during the years 2015 and 2016. Four breeds were used: Duroc (D), Yorkshire (Y), Landrace (L) and Pietrain (P). There was an effect (P <0.05) of the breed on total and progressive motility, ejaculate volume (vol) and total sperm cells. The effect of the breed was significant (P <0.05) on the spermatic kinetics variables except for amplitude of lateral head displacement (ALH, μm). We identified four sperm subpopulations (SPn) (P <0.05), SP1 (28.60%) characterized by low speed and non progressive movement, SP2 (20.54%) with movement very active and progressive, SP3 (16.12%) with moderate speeds and non-progressive trajectories, SP4 (34.74%) with active movement and higher progressiveness. The spermatic subpopulations disagree with generalized idea of the ejaculate as a unit and allowed to determine sperm groups by movement patterns and progressivity
Actas Iberoamericanas de Conservación Animal, vol.12 (2018):125-132
Keywords: Cerdos; Reproducción animal; Espermatozoides; Calidad del esperma; Cinética espermática